Marine species formation along the rise of Central America: The anomuran crab Megalobrachium. Issue 2 (23rd December 2019) - Hiller, Alexandra; Lessios, Harilaos A.
Abstract: The evolution of marine neotropical shallow water species is expected to have been greatly affected by physical events related to the emergence of the Central American Isthmus. The anomuran crab Megalobrachium, a strictly neotropical porcellanid genus, consists of four species in the West Atlantic (WA) and nine in the East Pacific (EP). Dispersal is limited to a relatively short planktonic phase, which lasts approximately two weeks. We obtained DNA sequences of three mitochondrial and two nuclear genes of all but one species of Megalobrachium to construct a time‐calibrated phylogeny of the genus and its historical phylogeography, based on the reconstruction of ancestral areas. The topology of the phylogenetic trees of Megalobrachium produced by Bayesian Inference (BI) and Maximum Likelihood (ML) were virtually congruent. The genus is monophyletic with respect to other porcellanids. Ancestral area reconstruction indicates that it arose in the eastern Pacific 18 million years ago and diversified into at least 13 species that are currently formally recognized and three additional species indicated by our data. Most morphological variation appears to have followed phylogenetic differentiation, though some cryptic speciation has also occurred. Four geminate clades in this genus implicate the gradual emergence of the Central American Isthmus in this diversification, but events preceding the final separation of the oceans as well as within‐ocean events after the cessation of water connections were also important.